From genes to animal behavior social structures, personalities, communication by color - Inoue-Murayama, Miho.; Inoue-Murayama, Miho.; Kawamura, Shoji; Weiss, Alexander; SpringerLink (Online service). (Tokyo New York Springer, 2011)
The biological and genetic bases of behavioral diversity have long been topics of study within many disciplines, including evolutionary biology, genetics, ethology, sociobiology, and comparative psychology, but only relatively recently have attempts been made to bring these different approaches together. This volume covers a wide range of interdisciplinary research which uses some of the newest and most promising methods and technologies. Presented here is an overview of findings in the ongoing search for the ultimate causes of behavior in several different species, including primates, dogs, r.
Includes bibliographical references and index.
Keywords: Electronic books